The role of calprotectin in giant cell arteritis - from pathophysiology to possible clinical applications - Kudraszew, Emilia; Roszkowski, Leszek; Ciechomska, Marzena; Wroński, Jakub (Frontiers in Immunology, 2025)
Giant cell arteritis (GCA) is an immune-mediated vasculitis predominantly affecting individuals aged 50 years and older, with clinical manifestations often overlapping with polymyalgia rheumatica (PMR). Despite advances in imaging and the advent of novel steroid-sparing agents, such as tocilizumab, challenges persist in accurately diagnosing and monitoring disease activity. Traditional inflammatory markers like C-reactive protein and erythrocyte sedimentation rate are frequently limited by their inability to fully capture disease dynamics, especially in patients receiving IL-6 inhibitors. In this context, calprotectin (CLP), a heterodimeric complex derived from S100A8/S100A9 proteins, has emerged as a promising biomarker due to its integral role in mediating inflammatory responses and its relative independence from IL-6 pathways. This review synthesizes current evidence on the biological functions of CLP in GCA pathogenesis, its potential utility in distinguishing between different clinical forms of the GCA-PMR spectrum, and its role in assessing disease activity and guiding therapeutic decisions. Furthermore, emerging CLP-targeted therapies in other inflammatory conditions may offer novel treatment avenues for GCA. Future research should focus on validating CLP as a predictive marker for relapse and refining its integration into clinical monitoring protocols to enhance patient outcomes.